The formation of the institute of presidency in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article discusses the historical, political and economic conditions of formation of the institute of presidency in the Republic of Kazakhstan, as well as the general characteristic and analyzes the characteristics of the president’s powers under the current legislation.Key words: Constitution of the Republic of Kazakhstan’s independence, sovereignty, the institute of presidency, democracy, constitutional reform.